The man from Penzance: Sir Humphry Davy (1778-1829) - Asfa-Wossen L. (The Institute of Materials, Minerals and Mining, 2015)
Davy saw science to be the ultimate truth. He loved the utility and permanence of it and the feeling of progression. He was a bold chemist and an inventor, but he thought like a writer